THE IMPLEMENTATION OF BIODIGESTER AS A SOURCE OF ECONOMIC GAIN IN THE MORRO GRANDE FARM, SOUTH MINAS GERAIS BRAZIL - Silva de Souza, Guilherme; Soares, Pedro Augusto (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Were analyzed during a technical visit carried out in the environmental engineering course at the State University of Minas Gerais at the Morro Verde farm located in the municipality of São João Batista do Glória, in the southern region of Minas Gerais (Brazil). The technologies implemented in the business were observed which, for that reason, are recognized in the national territory as examples of the applicability of sustainability in the economy. The farm has the production of biogas which is the fermentation process that leads to anaerobic digestion by bacteria resulting in the production of biogas (basically methane - CH4), this gas is transported to the energy generator that is used in the productive processes of the farm. All the organic matter generated by the cows is somehow reused on the farm, including the by-product generated after passing through the hydraulic press that is used as a form of fertilizer for planting. After adopting sustainability, the farm had a reduction of more than 90 thousand reais in energy consumption resulting from the photovoltaic energy panels and biogas production, proving that being sustainable is economically viable.